GINGIVECTOMY IN GINGIVAL ENLARGEMENT CASES USING CONVENTIONAL TECHNIQUE : Gingivektomi Pada Kasus Gingival Enlargement Menggunakan Teknik Konvensional - artika, Made deby (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Gingival enlargements is an abnormal condition that localized or generalized on the gingival cause by some factor. Gingival enlargements is always associated with chronic gingival irritation due to traumatic occlusion, calculus and the presence of rough edges on tooth restoration, drug induced or cause by systemic disease. Gingivectomy is an excision in the gingival area. By removing the pocket wall, gingivectomy provides visibility and accessibility to the removal of calculus as a whole. Case: A 12th years old men came to the Klungkung District Hospital complaining of a lump in the upper front gum since 6 months ago, clinically there was gingival swelling at 11,12,13,21,22,23. Case Treatment: The treatment procedure performed was gingivectomy with an conventional technic. Conventional Technic are used routinely for surgical procedures because predictable result. Example for Growth excision, excision or incision biopsy, white lesion ablation, and gingivectomy are common in intraoral procedures. Discussions: The results of treatment after one week and two weeks showed good condition with slight complaints of pain. Conclusion: The gingivectomy technique in this case was performed using a continuous technique because the gingival enlargement was found in the marginal and interdental areas. The results of treatment for more than a week show good condition.